Peran Negara dalam Perekonomian (Tinjauan Teoritis Kebijakan Fiskal dalam Ekonomi Islam) - Syaakir Sofyan (Hunafa: Jurnal Studia Islamika, 2016)
Indonesia is a state based on law and adopts welfare. Thus, the state has an obligation and responsibility to realize public welfare as stated in the fourth paragraph of Undang-Undang Dasar (UUD) Negara Republik Indonesia 1945. In achieving these objectives, the government must play an important role in various aspects of community life, especially in the economy. One form of government intervention, namely in fiscal policy by adjusting the state revenues and expenditures in the state budget. In Islamic economics, fiscal policy objective is to create economic stability, high economic growth and equitable distribution of income, coupled with the other objectives contained in the rules of Islam